Novel individual location recommendation with mobile based on augmented reality - Zhenghao Shi; Hao Wang; Wei Wei; Xia Zheng; Minghua Zhao; Jinwei Zhao; Yinghui Wang (International Journal of Distributed Sensor Networks)
Location-based services for mobile users provide a convenient means of filtering information based on current geographical position. However, the information in traditional location service systems is provided through an abstract metaphor that the user has to understand and translate into action. In this paper, a mobile augmented reality-based system for individual location recommendation is proposed. The system consists of the modules of user location, marker detection, three-dimensional (3D) display and location guide by combing augmented reality with navigation technology. Through such a system, the position and orientation information from any sensory source were pervasively extracted and used to enhance the association to the real world by combining video techniques and 3D-graphics in an augmented reality view. Experimental results demonstrate that the proposed system is both efficient and effective in helping people locate their position. Compared with the traditional Global Positioning Systems-based location services system, the proposed system can also enhance users’ senses experience by providing users with a more intuitive, 3D, dynamic information display and sharing capabilities.